Success of Process Innovations Through Active Works Council Participation - Breitling, Kai; Scholl, Wolfgang (Frontiers in Psychology, 2022)
Successful innovations are deemed to be a necessary requisite for enterprise success. On the other hand, works council participation (“co-determination” in Germany) and employee participation are judged differently as either fostering employee and enterprise benefits or only the former or even none. Both forms of participation have found diverging theoretical and empirical argumentations regarding innovations. Here, we argue and show empirically that both forms of participation deliver positive contributions to innovation success, economically and employee-related, substantiated with qualitative reports from 36 process innovation cases and quantitative data from 44 cases. Qualitative case analyses reveal different profiles of works council participation depending on the innovation type. Independent of the innovation types, more successful innovations are marked by more intensive participation. Quantitative examinations of a causal model with path analysis specify how this is achieved: Works council and employee participation further the growth of appropriate knowledge and the former also raises the coordination capability; both are essential preconditions for innovation success. A direct impact of works councils on innovation success complements the indirect effects. The slightly modified path analysis explains 53% of the innovation success variance.